Implementation of the Principle of Strict Liability Through Civil Law Enforcement to Protect and Manage the Environment - Rizqa Maulidya; Munawir; Mulazi Ibna Fikra; Hikmah Amna Mnr; Muhammad Hatta (International Journal of Law, Social Science, and Humanities, 2025)
The settlement of environmental disputes currently uses the principle of Liability based on Fault which requires the plaintiff to prove the element of fault of the defendant. The elimination of the principle of Strict Liability as regulated in Article 88 of Law Number 32 of 2009 concerning Environmental Protection and Management brings significant changes in the process of resolving environmental disputes. The purpose of this study is to determine the urgency of implementing the principle of Strict Liability and to analyze the legal implications of eliminating the principle of Strict Liability as an effort to resolve environmental disputes. This study uses a normative legal research method with a statute approach, a conceptual approach, and a comparative approach. The purpose of the study is to explain the concept of strict liability and its legal basis, describe civil law in environmental cases, and assess the effectiveness of strict liability in protecting the environment. The principle of strict liability is an important tool in environmental law to enforce responsibility for environmental pollution and damage without having to prove fault. Civil law enforcement can be an effective instrument if supported by a strong judicial system and public awareness.